In Vitro and In Vivo Evaluation of Vancomycin-Loaded PMMA Cement in Combination with Ultrasound and Microbubbles-Mediated Ultrasound. (6th January 2015) - Lin, Tiao; Cai, Xun-Zi; Shi, Ming-Min; Ying, Zhi-Min; Hu, Bin; Zhou, Chen-He; Wang, Wei; Shi, Zhong-Li; Yan, Shi-Gui
Abstract : Ultrasound (US) has been used to increase elution of antibiotic from an antibiotic-loaded poly(methyl methacrylate) (PMMA) bone cement (ALBC). We aimed to further investigate whether microbubbles-mediated US (US + MB) facilitate elution of vancomycin (VAN) from cylindrical specimens and enhance the activity of the eluted antibiotic against Staphylococcus aureus ( S. aureus ) in vitro. The study groups comprised cylindrical bone cement fabricated with VAN (VAN), ALBC using US (VAN + US), and ALBC using MB-mediated US (VAN + US + MB). We also carried out an in vivo study involving the activity of VAN from cylindrical cement implanted in tibiae of New Zealand white rabbits inoculated with S. aureus . We found that (1) in vitro, elution from VAN + US + MB cylinders was significantly higher than from either the VAN or VAN + US specimens; (2) the activity of the eluted VAN from the VAN + US + MB cylinders against planktonic S. aureus was significantly higher than from either the control or VAN or VAN + US specimens; and (3) in the rabbits, the activity of the eluted VAN from the VAN + US + MB cylinders against S. aureus was significantly higher than from either the control or VAN or VAN + US specimens. The present results suggest that VAN-loaded PMMA cement irradiated with MB-mediated US may have a role in controlling prosthetic joint infection.